1951
DOI: 10.1152/ajplegacy.1951.166.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Crossed Phrenic Phenomenon

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1956
1956
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…This type of injury compromises direct (monosynaptic) projections from the ventral respiratory column in the medulla to ipsilateral phrenic motoneurons (Ellenberger and Feldman, 1988; Ellenberger et al, 1990; Keomani et al, 2014; Lane et al, 2009b; Lane et al, 2008; Vinit and Kastner, 2009a), and results in an ipsilateral hemidiaphragm paralysis (Figure 1). Despite the extent of injury, acute partial recovery of phrenic and hemidiaphragm activity after C2Hx can be accomplished by a subsequent contralateral phrenicotomy (Goshgarian, 2003a; Porter, 1895) or by inducing a respiratory stress such as asphyxia, hypoxia or hypercapnia (Golder and Mitchell, 2005; Lewis and Brookhart, 1951). This type of post-injury plasticity - known as the “cross-phrenic phenomenon” (CPP) – is attributed to activation of contralateral (spared), normally latent, bulbospinal pathways that cross the spinal midline below the injury (Figure 1A) (Goshgarian et al, 1991; Moreno et al, 1992).…”
Section: Plasticity After Cervical Scimentioning
confidence: 99%
“…This type of injury compromises direct (monosynaptic) projections from the ventral respiratory column in the medulla to ipsilateral phrenic motoneurons (Ellenberger and Feldman, 1988; Ellenberger et al, 1990; Keomani et al, 2014; Lane et al, 2009b; Lane et al, 2008; Vinit and Kastner, 2009a), and results in an ipsilateral hemidiaphragm paralysis (Figure 1). Despite the extent of injury, acute partial recovery of phrenic and hemidiaphragm activity after C2Hx can be accomplished by a subsequent contralateral phrenicotomy (Goshgarian, 2003a; Porter, 1895) or by inducing a respiratory stress such as asphyxia, hypoxia or hypercapnia (Golder and Mitchell, 2005; Lewis and Brookhart, 1951). This type of post-injury plasticity - known as the “cross-phrenic phenomenon” (CPP) – is attributed to activation of contralateral (spared), normally latent, bulbospinal pathways that cross the spinal midline below the injury (Figure 1A) (Goshgarian et al, 1991; Moreno et al, 1992).…”
Section: Plasticity After Cervical Scimentioning
confidence: 99%
“…The significant increase in the drive to breathe activated a latent pathway that restored function to the hemidiaphragm paralyzed by hemisection and was later termed the ''crossed phrenic phenomenon'' (37). Further examination revealed that the amount of activity recorded from the previously paralyzed hemidiaphragm was proportional to the intensity of the respiratory drive (38). The presence of the crossed phrenic phenomenon has since been confirmed in dogs (37)(38)(39), cats (37)(38)(39)(40)(41), rabbits (37,(41)(42)(43), guinea pigs (44,45), rats (35,(46)(47)(48), mice (49), and even woodchucks (37).…”
Section: History Of the Crossed Phrenic Phenomenonmentioning
confidence: 99%
“…In this model a cervical spinal cord hemisection interrupts the major descending respiratory pathways and paralyzes the hemidiaphragm ipsilateral to hemisection. Subsequent transection of the phrenic nerve contralateral to the hemisection induces asphyxia, which enhances central respiratory drive and, thus, activates the latent respiratory motor pathway, reestablishing function to the hemidiaphragm paralyzed by hemisection [267]. Activation of the latent respiratory motor pathway can also be achieved pharmacologically by the application of antagonist of adenosine receptor type 1 and agonists of adenosine receptor type 2 [268,269] as well as serotonergic agonists [270,271] by a mechanism mediated by the 5-HT2 receptor [272].…”
Section: Spinal Cord Injurymentioning
confidence: 99%